Analysing Impacts of Preferential Trade Agreements toward International Rule-Based Trading System - Abdul Razak Nasution (Budapest International Research and Critics University, 2021)
International economic law was born in line with the development of international economic relations. International economic law can continue to exist because it is needed by every country in participating in the international arena to expand its market share. The change in the international trade system towards liberalization, such as ASEAN becoming the ASEAN Economic Community at the end of 2015, creates many opportunities as well as challenges for Indonesia's balance of payments condition. The opportunity in question is that Indonesia can expand its market reach to other ASEAN countries. Another positive impact of the existence of the AEC is that Indonesian investors can expand their investment reach abroad, and vice versa, Indonesia can also attract investors from other ASEAN countries to invest in Indonesia. Meanwhile, the challenge is, with the level of trade competition getting tighter, the greater the trade balance deficit between Indonesia and other ASEAN countries, and how Indonesia can increase its investment attractiveness. This study was conducted to determine the impact of the ASEAN Economic Community (AEC) on Indonesia's Balance of Payments in 2017. From the results of data analysis, in 2016, there was a decrease in the number of exports of goods from USD 148,365 million in 2015, to USD 144,441 million in 2016. The services trade balance deficit in 2016 decreased to USD6.5 billion from USD8.7 billion in 2016.